Self-disclosure of Men Having Sex with Men (MSM) as an Effort to Prevent HIV and AIDS - Putri, Dhea Ninda; Rif'ah, Erwin Nur; Rokhmah, Dewi (Jurnal Promosi Kesehatan Indonesia, 2025)
Background: The HIV epidemic in Indonesia is still a major health problem, especially among men who have sex with men (MSM). The high prevalence of HIV in MSM is influenced by fear of stigma, discrimination, or negative consequences. Self-disclosure is an important aspect of efforts to prevent HIV and AIDS, but there are still MSM who experience obstacles related to self-disclosure.Method: This study uses a qualitative approach with a phenomenological method. The main informants consisted of 10 MSM domiciled in the Jember Regency, selected using the snowball technique. Source triangulation was carried out by involving HIV and AIDS NGO companions, peers, partners, and health workers. Data collection was carried out through in-depth interviews, while data analysis used the Interpretative Phenomenological Analysis (IPA) method.Result: The results of the study showed that self-disclosure in MSM was influenced by several main factors, namely motivation, intensity, accuracy of feedback, time, and depth and breadth of information shared. The majority of informants felt comfortable opening up to peers and MSM friends compared to family or health workers. Negative feedback from the social environment tended to inhibit openness, while positive support could increase motivation to share information. This study emphasizes the importance of a supportive environment, especially in health services, to increase openness in HIV and AIDS prevention efforts. A supportive environment, especially in health services, is essential to increase openness in HIV and AIDS prevention efforts. The suggestion given is to conduct health promotion to increase self-disclosure of MSM in preventing HIV and AIDS, which can be done through education, social support, and increasing access to health services